Review on Proton Radioactivity in the Actinide Region: Experimental status, Theoretical Approaches and Future perspectives (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Proton radioactivity is one of the most distinctive manifestations of quantum tunnelling in atomic nuclei and provides a powerful probe of nuclear structure beyond the proton drip line. Since its theoretical prediction by Goldanskii in 1960 and subsequent experimental confirmation, proton emission has become an important spectroscopic tool for investigating single-particle configurations, shell evolution, nuclear deformation, and the interplay between nuclear and Coulomb interactions in proton-rich systems. While proton radioactivity has been extensively studied in light, medium-mass, and rare-earth nuclei, comparatively little attention has been devoted to the actinide region despite its unique structural and decay properties.This review presents a comprehensive overview of proton radioactivity in actinide nuclei (89 ≤ Z ≤ 103), with emphasis on recent theoretical developments and future experimental prospects. The historical evolution of the field, experimental status, theoretical models, and decay systematics are critically discussed. Particular attention is given to the prediction of proton-emitting actinides, the influence of proton-decay energy and quantum tunnelling on half-lives, Geiger–Nuttall-type correlations, and the competition between proton emission, α decay, β decay, spontaneous fission, and cluster radioactivity. The predictive performance of widely used theoretical approaches, including the Coulomb and Proximity Potential Model (CPPM), Generalized Liquid Drop Model (GLDM), Effective Liquid Drop Model (ELDM), Density-Dependent Michigan 3-Yukawa (DDM3Y) interaction, Jeukenne–Lejeune–Mahaux (JLM) interaction, and related microscopic models, is also evaluated.The review highlights the most promising candidate proton emitters in the actinide region and discusses the prospects for their experimental observation using next-generation rare-isotope facilities. By integrating current theoretical predictions with available experimental knowledge, this article provides a comprehensive assessment of proton radioactivity in heavy nuclei and underscores its importance for understanding the limits of nuclear stability and the structure of proton-rich actinides.